2014
DOI: 10.1155/2014/213283
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Primary Hyperparathyroidism due to Intrathyroidal Parathyroid Cyst

Abstract: Parathyroid cysts constitute 0.08–3.41% of all parathyroid masses. Intrathyroidal parathyroid cysts, however, are rare conditions with only a few cases being reported. Most of the parathyroid cysts are found to be nonfunctional and functional cysts are generally thought to be due to cystic degeneration of parathyroid adenomas. A cystic, smooth contoured lesion of 24 × 19 × 16 mm was observed in left thyroid lobe of a 76-year-old woman during ultrasonography which was performed as routine workup for primary hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…In addition, ultrasonography does not provide any information about whether these cysts arise from the parathyroid or thyroid glands, which makes identifying the cystic mass as a parathyroid adenoma difficult (5). The intracystic iPTH levels in fine-needle aspirates are useful for determining whether a cyst is a parathyroid cyst, thyroid cyst, or nonfunctional cyst (6)(7)(8). However, before performing fineneedle aspiration, determining whether or not the cyst is related to parathyroid cancer is important because fine-needle aspiration is contraindicated in parathyroid cancer due to the risk of seeding along the needle tract (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, ultrasonography does not provide any information about whether these cysts arise from the parathyroid or thyroid glands, which makes identifying the cystic mass as a parathyroid adenoma difficult (5). The intracystic iPTH levels in fine-needle aspirates are useful for determining whether a cyst is a parathyroid cyst, thyroid cyst, or nonfunctional cyst (6)(7)(8). However, before performing fineneedle aspiration, determining whether or not the cyst is related to parathyroid cancer is important because fine-needle aspiration is contraindicated in parathyroid cancer due to the risk of seeding along the needle tract (10).…”
Section: Discussionmentioning
confidence: 99%
“…Positive findings on 99m technetium ( 99m Tc) sestamibi scans of functional parathyroid cysts are less frequent than for non-cystic parathyroid adenomas (4), and ultrasonography is not effective at distinguishing between cysts with parathyroid origins and those with thyroid origins (5); therefore, identifying cystic parathyroid adenomas is challenging. However, measuring intracystic PTH levels in fine-needle aspirates from cysts is useful for diagnosing functional parathyroid cysts (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Other cases can be found in the tracheoesophageal sulcus, posterior esophageal area, inferior thyroid pole, heart, etc. Based on the histopathology, PA can be divided into solid PA and cystic PA. Studies have suggested that functional parathyroid cysts may be the result of parathyroid adenoma cysts [6,7] . Therefore, cystic PAs are also called functional parathyroid cysts.…”
Section: Discussionmentioning
confidence: 99%
“…According to a previous large series, intrathyroidal PAs account for 1% of all PAs [5]. Cystic intrathyroidal PAs are even rarer, with a few cases described in the literature so far [6][7][8]. The rarity of this entity makes the pre-operative diagnosis elusive.…”
Section: Discussionmentioning
confidence: 99%